Adenosine deaminase regulates Treg expression in autologous T cell-dendritic cell cocultures from patients infected with HIV-1. Issue 2 (26th August 2015) - Naval-Macabuhay, Isaac; Casanova, Víctor; Navarro, Gemma; García, Felipe; León, Agathe; Miralles, Laia; Rovira, Cristina; Martinez-Navio, José M; Gallart, Teresa; Mallol, Josefa; Gatell, José M; Lluís, Carme; et al.
Abstract : Counteracting immunosuppression due to HIV-1 by ADA-mediated increase of effector responses in autologous T cells, co-cultured with HIV-1-presenting cells. Abstract: Regulatory T cells have an important role in immune suppression during HIV-1 infection. As regulatory T cells produce the immunomodulatory molecule adenosine, our aim here was to assess the potential of adenosine removal to revert the suppression of anti-HIV responses exerted by regulatory T cells. The experimental setup consisted of ex vivo cocultures of T and dendritic cells, to which adenosine deaminase, an enzyme that hydrolyzes adenosine, was added. In cells from healthy individuals, adenosine hydrolysis decreased CD4 + CD25 hi regulatory T cells. Addition of 5′- N -ethylcarboxamidoadenosine, an adenosine receptor agonist, significantly decreased CD4 + CD25 lo cells, confirming a modulatory role of adenosine acting via adenosine receptors. In autologous cocultures of T cells with HIV-1-pulsed dendritic cells, addition of adenosine deaminase led to a significant decrease of HIV-1-induced CD4 + CD25 hi forkhead box p3 + cells and to a significant enhancement of the HIV-1-specific CD4 + responder T cells. An increase in the effector response was confirmed by the enhanced production of CD4 + and CD8 + CD25 − CD45RO + memory cell generation and secretion of Th1 cytokines, including IFN-γ and IL-15 and chemokines MIP-1α/CCL3, MIP-1β/CCL4, and RANTES/CCL5. These ex vivo results show, in a physiologically relevant model, that adenosine deaminase is able to enhance HIV-1 effector responses markedly. The possibility to revert regulatory T cell-mediated inhibition of immune responses by use of adenosine deaminase, an enzyme that hydrolyzes adenosine, merits attention for restoring T lymphocyte function in HIV-1 infection.